Intense shear induced caterpillar-like continuous hierarchical fiber enhanced poly(butylene succinate) biocomposite towards strong mechanical performance. (1st November 2020) - Zhao, Liang; Hu, Lingquan; Lin, Panlong; Yu, Qiao; Han, Qianqian; Huang, Shiqi; Zhang, Bin; Yin, Xianze; Wu, Jing; Yang, Feihua; Zhan, Jiayu; Wang, Hua; et al.
Abstract: Herein, we used intense shear to construct caterpillar-like continuous hierarchical fibers (CLCHF). This architecture was then modified with mussel inspired poly(dopamine) (PDA) and γ-methacryloxypropyl trimethoxy silane (KH570) in a one-step method. Finally, employing (PDA + KH570)@CLCHF and compounded with poly(butylene succinate) (PBS) ultrafine fiber, (PDA + KH570)@CLCHF/PBS biocomposite was manufactured by combining intense shear and thermal-compression method. In virtue of intense shear, CLCHF can be effectively produced with nanoscale fibrils from 2 nm to 28 nm and (PDA + KH570)@CLCHF and PBS ultrafine fibers displayed favorable homogenization in aqueous solution. More importantly, the interspace between (PDA + KH570)@CLCHF and PBS ultrafine fibers could be optimized to facilitate infiltration at high filler content in polymers. The results also showed that the PBS biocomposite with 30 wt% (PDA + KH570)@CLCHF displayed optimal mechanical performance. Its tensile strength, elastic modulus, flexural strength, flexural modulus and impact strength reached to 120.2 MPa, 6.4 GPa, 110.1 MPa, 4.0 GPa and 23.5 kJ/m 2, respectively. It is noticeble that the tensile properties were superior to some previously reported PBS biocompoistes due to the ability of CLCHF to effectively hinder the aggregation of numerous microcracks and slow crack tip propagation. The (PDA + KH570)@CLCHF/PBS biocomposites reported here can be used as desirable substitutes for nondegradable composites due to its high value added and favorable mechanical performance, and may broaden the application prospect of PBS biocomposite.